Autokorelasi Spasial Densifikasi Bangunan di Kota Pontianak - Wulandari, Agustiah; Purnomo, Yudi (Prodi Arsitektur Universitas Matana, 2025)
Pontianak, the capital of West Kalimantan Province, possesses unique characteristics that set it apart from other Indonesian cities. The city exhibits distinct characteristics compared to other cities in Indonesia. Pontianak is the focus of this study due to its significant urban growth, which necessitates an in-depth analysis to support sustainable urban planning. The ongoing densification of buildings in Pontianak and population growth impact the land required to support daily activities. This research seeks to specify and analyze the spatial distribution patterns of building densification in Pontianak using spatial autocorrelation. The study utilized a quantitative analysis method. The data comprises building distribution and area data sourced from Open Street Map (O.S.M.). These data were analyzed using Spatial Autocorrelation Analysis techniques, specifically Moran's I Index and Local Indicators of Spatial Autocorrelation (L.I.S.A.). The analysis strives to define the patterns of relationships or correlations between building locations in Pontianak. The examination results indicated that Moran's I Index is 0.762, signifying a positive spatial autocorrelation of buildings in Pontianak. It suggests that similar-sized buildings cluster together. The L.I.S.A. analysis further revealed that the Pontianak Kota District predominantly falls within the High-High category, indicating that buildings with high spatial potential surround this district. Additionally, the Pontianak Kota District is identified as the City Service Center (PPK) according to the Pontianak City Spatial Plan (R.T.R.W.) for 2013-2033. These findings demonstrate a significant correlation between the distribution of buildings and their areas within Pontianak City.